Impacts of Emergency Medical Technician Configurations on Outcomes of Patients with Out-Of-Hospital Cardiac Arrest - Mohammd Mashi Genef Alanze . Eid Farhan Naif Al Anazi . Mshari Madhor Fawaz Aldahmashi Majd Hazza Matab Bn Bseais . Shaker Mater Hazzaa Alshammari . Nasser Rashid Abdulaziz Al-Mutairi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
The role of emergency medical technicians (EMTs) in providing advanced life support (ALS) for out-of-hospital cardiac arrest (OHCA) patients is crucial, yet the optimal EMT configuration remains a topic of debate. This three-year cohort study focused on non-traumatic OHCA adults treated by ALS teams , utilizing an Utstein-style population database. The study examined the impact of the EMT-paramedic (EMT-P) ratio, defined as the proportion of EMT-Ps among on-scene EMTs, on patient outcomes. Among 1357 eligible cases, the median number of on-scene EMTs was 2, with an EMT-P ratio ranging from 50% to 100%. Multivariate analysis identified several predictors of sustained return of spontaneous circulation (ROSC), including younger age, witnessed cardiac arrest, prehospital ROSC, prehospital defibrillation, and comorbid diabetes mellitus. After adjusting for confounders, each 10% increase in the EMT-P ratio was associated with an 8% higher chance of sustained ROSC (adjusted odds ratio [aOR], 1.08; p < 0.01) and a 12% higher likelihood of favorable neurologic status at discharge (aOR, 1.12; p = 0.048). Conversely, the number of on-scene EMTs did not significantly impact outcomes. This study underscores the importance of EMT-P ratio in improving outcomes for non-traumatic OHCA adults, highlighting the potential benefits of optimizing EMT configurations.